Tradisi Pelayaran Suku Bajo Sebagai Warisan Maritim Indonesia - Yohanis Kristianus Tampani; Augusta De Jesus Magalhaes; Natalia Bulu Masan; Simon Ukasa Manek; Selfina Eliseba Manuni; Adriana Hoar Ulu; Stanislaus Aristo Nana (SOSIAL : Jurnal Ilmiah Pendidikan IPS, 2026)
The Bajo people are one of the most prominent nomadic seafaring communities in Southeast Asia, having inhabited the Indonesian waters for centuries. This study aims to comprehensively examine the Bajo people's seafaring traditions as an integral part of Indonesia's maritime heritage that urgently needs to be systematically preserved amidst the increasingly rapid flow of modernization and globalization. This study uses a qualitative approach with a descriptive analytical literature study method, namely by systematically collecting, reviewing, and synthesizing relevant academic literature, historical documents, ethnographic reports, government policy documents, and previous research findings related to the maritime traditions of the Bajo community. The results of the study reveal that the Bajo people's seafaring traditions encompass several core dimensions such as the pabbiritang star navigation system that utilizes more than 40 constellations and traditional navigation including lepa-lepa, soppe, and bidi-bidi. These traditions are currently facing serious threats from the government's sedentarization policy, technological modernization, marine environmental degradation, and the failure of knowledge transmission across generations. This study concludes that preserving the Bajo maritime heritage requires an integrated approach that combines systematic scientific documentation, legal recognition of customary maritime rights, community-based education programs, and alternative livelihoods that are economically sustainable while respecting their cultural identity.